2014
DOI: 10.1007/s00464-014-3835-9
|View full text |Cite
|
Sign up to set email alerts
|

Robotic right colectomy with intracorporeal anastomosis compared with laparoscopic right colectomy with extracorporeal and intracorporeal anastomosis: a retrospective multicentre study

Abstract: Performing the RRCIA offers significantly better perioperative recovery outcomes compared with the LRCEA, with a substantial reduction in the length of the hospital stay. The RRCIA does not offer the same advantages compared with the LRCIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 28 publications
5
88
1
Order By: Relevance
“…Milone et al [16] matched the control group using a propensity score. Trastulli et al [18] reported a retrospective multicenter case series on right colectomy comparing robotic intracorporeal anastomosis to laparoscopic intracorporeal anastomosis and laparoscopic extracorporeal anastomosis. The included studies resulted in a total number of 1492 participants who underwent a laparoscopic right hemicolectomy further specified to 763 and 729 patients for intra- or extracorporeal anastomosis, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Milone et al [16] matched the control group using a propensity score. Trastulli et al [18] reported a retrospective multicenter case series on right colectomy comparing robotic intracorporeal anastomosis to laparoscopic intracorporeal anastomosis and laparoscopic extracorporeal anastomosis. The included studies resulted in a total number of 1492 participants who underwent a laparoscopic right hemicolectomy further specified to 763 and 729 patients for intra- or extracorporeal anastomosis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In nine studies, the intracorporeal performed anastomosis was created using a mechanical stapler with [1315, 17–19, 33, 35, 36] or without [16] additional sutures in the IA technique. A mechanical stapler was most commonly used for the extracorporeal anastomosis as well (with [13, 14, 18, 36] or without [16, 19] additional sutures). One study made a hand-sewn anastomosis [15] or according to the preference of the individual surgeon (mechanical or hand-sewn) [17, 33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative conversion rates were statistically significantly lower among patients undergoing RC. Reasons for conversion included the presence of extensive intraabdominal adhesions, the local extension of the neoplasm [33], hemorrhage from the paraduodenal veins that could not be effectively controlled, intraoperative bleeding due to an injury in the left renal vein [25], obesity with a bulky colonic mesentery and fatty omentum [26], and technical difficulties that included stapler misfiring. In assessing the rate of conversion to laparotomy, a history of previous abdominal surgery in a patient can be a confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with a higher proportion of patients who have had prior surgery may have a higher rate of conversions because of the presence of adhesions and scarring. Transtulli et al [33] attempted to address this issue in their study. Their study showed that of the four robotic procedures converted (conversion rate: 3.9%), 47 patients had a history of previous abdominal surgery (previous abdominal surgery rate: 46.7%).…”
Section: Discussionmentioning
confidence: 99%